Zn-modified ceria as a redox material for thermochemical H2O and CO2 splitting: effect of a secondary ZnO phase on its thermochemical activity. Issue 14 (18th March 2016) - Lin, Fangjian; Samson, Vallerie A.; Wismer, Andrea O.; Grolimund, Daniel; Alxneit, Ivo; Wokaun, Alexander
Abstract : A detrimental effect of a secondary ZnO phase in Zn-modified ceria on its activity for thermochemical H2 O and CO2 splitting is elucidated. Abstract : Two-step thermochemical cycles based on ceria (CeO2 ) are a promising way to store dilute and intermittent solar energy by producing chemical fuels (solar fuels) such as H2 and CO from H2 O and CO2 with concentrated solar radiation. Many studies have shown that the fuel yield per cycle can be enhanced by introducing certain heterocations (dopants) into the ceria lattice. In this study, dual-phase Zn-modified ceria synthesized by coprecipitation was investigated as a redox material for thermochemical H2 O and CO2 splitting. Surprisingly, the material exhibits significant increase of the H2 and CO productivities during the first few cycles, in contrast to an anticipated decrease of activity due to sintering. Data suggests that the material's solar fuel productivity eventually stabilizes and exceeds that of native ceria. To elucidate the cause of this observation, changes of the material's physicochemical properties during the initial cycles were analysed in detail. The chemical compositions and elemental distribution were probed using X-ray fluorescence (XRF) spectroscopy with lab and synchrotron X-ray sources. The observed increase of productivity during the initial cycles is correlated with a significant loss of zinc through ZnO sublimation, suggesting a negative effect of the secondary ZnO phase in Zn-modified ceria for its thermochemical activity. Structural changes were revealed by synchrotron micro X-ray powder diffraction (μ-XRD) and X-ray absorption spectroscopy (XAS). The zinc that remains incorporated in the ceria lattice after the initial cycles is likely to be responsible for its higher thermochemical activity in comparison to native ceria.